COGNITIVE BENEFITS OF MULTILINGUALISM IN EFL LEARNERS: IMPLICATIONS FOR LANGUAGE ACQUISITION AND ACADEMIC PERFORMANCE - Rustamova M.A. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article explores the cognitive benefits of multilingualism in English as a Foreign Language (EFL) learners and its influence on language acquisition and academic performance. The study is based on a qualitative literature review in the fields of second language acquisition (SLA), cognitive psychology, and bilingual education. It examines how multilingual experience influences cognitive functions such as working memory, attention control, cognitive flexibility, and metalinguistic awareness. Previous research shows that multilingual learners often demonstrate stronger cognitive control and better ability to manage complex learning tasks compared to monolingual learners. These cognitive advantages can support faster language learning, improved problem-solving skills, and higher academic achievement. However, research also shows that these effects depend on language proficiency level, frequency of language use, and learning environment. The article concludes that multilingualism should be viewed as a valuable cognitive resource in EFL education that can positively support both language learning and academic performance.